Commercial pressure offloading insoles: dynamic stability and plantar pressure effects while negotiating stairs. (4th May 2019) - Antonio, Patrick J.; Perry, Stephen D.
Abstract : Diabetic peripheral neuropathy (DPN) is a dysfunction of the peripheral nerves that restricts sensation from the feet, compromising an individual's mobility and balance. Individuals with DPN generate elevated (from typical) values of foot pressure while walking often leading to tissue ulcerations. Currently, there are commercial pressure offloading (CPO) insoles that claim to reduce foot pressure and limit ulcer formation; however, the insoles' capacity to reduce pressures during common activities have not been examined. The aim of this study was to observe the effects of various insoles on balance and plantar pressure while negotiating stairs, in individuals with diabetes. Twenty-nine (29) participants (14 individuals with diabetes, and 15 age-matched controls) were instructed to traverse a seven-step staircase while wearing three CPO insoles and one normal insole. Spatial and temporal balance (COM-BOS) and foot peak pressures (overall foot and regions of interest) were recorded using pressure insoles placed inside standardized footwear. Overall foot peak pressures across insoles were not significantly different. With respect to the (spatial) COM-BOS lateral distance, the normal insoles had the smallest lateral distance (mean = 0.08 m) among all insole conditions during descent. Aetrex (mean = 0.09 m) and Prothotics insoles (mean = 0.09 m) during descent had greater lateral distances than normal insoles. Further, the temporal balance demonstrated a shorter time while wearing normal insoles (1.7 sec) compared to Prothotics insoles (1.9 sec). CPO insoles worn by individuals with diabetes did not significantly offload pressure compared to normal insoles. With respect to balance, descending the stairs wearing normal insoles may place an individual at a greater risk of imbalance, while the Prothotics insole may prove to be a better option.